2017
DOI: 10.4103/tjo.tjo_19_17
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal intraocular lenses: Types, outcomes, complications and how to solve them

Abstract: The multifocal intraocular lenses (IOLs) available are often able to restore visual function and allow spectacle independence after their implantation with great levels of patient satisfaction. The factors associated with the postoperatory success include the careful selection of the patient, the knowledge about the IOLs’ design, and their visual performance added to the proper surgical technique and management of possible complications as demonstrated by the evidence available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 16 publications
0
33
0
4
Order By: Relevance
“… 24 The reported dynamic pupil size has got major clinical implications in our studied population, most importantly while choosing pupil-dependent multifocal IOLs. 25 , 26 Furthermore, both pupil size and Z4 are key factors for optimized aspheric IOL implantation. 27 Paucity of studies on our population that determine such parameters validated the aim of our study, especially with the relevant clinical implications that would make benefit from the normative values of such parameters.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The reported dynamic pupil size has got major clinical implications in our studied population, most importantly while choosing pupil-dependent multifocal IOLs. 25 , 26 Furthermore, both pupil size and Z4 are key factors for optimized aspheric IOL implantation. 27 Paucity of studies on our population that determine such parameters validated the aim of our study, especially with the relevant clinical implications that would make benefit from the normative values of such parameters.…”
Section: Discussionmentioning
confidence: 99%
“…With a single focal point, monofocal IOLs are effective in restoring satisfactory distance vision; however, most patients require spectacle correction for intermediate and near vision, even after surgery [1, 2]. Thus, multifocal IOLs were designed to meet the increasing demand from patients for spectacle independence [3]. For providing far, intermediate and near vision simultaneously, multifocal IOLs possess two or more independent focal points, which result in contrast reduction and increased photic phenomena, thus reducing visual quality [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MIOLs are comparable to monofocal IOLs for distance vision but are more effective for near vision and provide greater spectacle independence. 24 Based on the focality, MIOLs are classified as either bifocal (2 foci) or trifocal (3 foci). 5…”
mentioning
confidence: 99%
“…Although MIOLs are more frequently associated with photic disturbances than monofocal IOLs, the trifocals IOLs have improved performance in photic phenomena than bifocal IOLs. 4,6,7 More recently, extended depth of focus (EDOF) IOLs, a new class of IOLs have been introduced. The EDOF IOLs elongate a single focal point over a range of distance using diffractive optics, thus providing better intermediate performance than monofocal IOLs.…”
mentioning
confidence: 99%